2015
DOI: 10.1111/jgh.12723
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of oxidative stress and improvement of liver functions in mice by ursolic acid via LKB1‐AMP‐activated protein kinase signaling

Abstract: UA via LKB1-AMPK signaling offers protective effects on BDL-induced liver injury in mice, which may be related to inhibition of oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…Acetylcholine also provides cardioprotection against hypoxia/reoxygenation injury in a cellular model through an AMPK/PGC1‐ α ‐involved mechanism that increases mitochondrial density, mass, and mtDNA copy number . In a variety of experimental liver fibrosis models, curcumin , adiponectin , and ursolic acids have been utilized to exert protective effects via LKB1‐AMPK signaling activation. Moreover, melatonin was recently shown to improve steatotic liver graft preservation via AMPK‐mediated autophagy activation .…”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholine also provides cardioprotection against hypoxia/reoxygenation injury in a cellular model through an AMPK/PGC1‐ α ‐involved mechanism that increases mitochondrial density, mass, and mtDNA copy number . In a variety of experimental liver fibrosis models, curcumin , adiponectin , and ursolic acids have been utilized to exert protective effects via LKB1‐AMPK signaling activation. Moreover, melatonin was recently shown to improve steatotic liver graft preservation via AMPK‐mediated autophagy activation .…”
Section: Discussionmentioning
confidence: 99%
“…It is well‐accepted that the crucial proteins, including CD36 and CPT‐1, which are in charge of mediating FFA uptake and oxidation, are regulated by AMPK activation . Studies have reported that AMPK activation is involved in UA‐induced apoptosis of cancer and improvement of liver function . However, whether and how AMPK pathway mediates UA‐stimulated skeletal muscle FFA catabolism is also not well identified so far.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence showing a beneficial role of AMPK activation in reducing hepatic fibrosis, improving liver function, and lowering hepatocytotoxicity (Liang et al, 2017). In addition, several novel drug candidates for the treatment of hepatic fibrosis, including metformin, betulin, berberine, cucurbitacin E, and curcumin, have been shown to act via increased AMPK signaling (Xu et al, 2003;Fu et al, 2008;Yang et al, 2015;Wu et al, 2016;Liang et al, 2017). Moreover, AMPK signaling is known to negatively regulate mTOR, an atypical serine/threonine kinase shown to play an important role in the regulation of cell growth, differentiation, migration, and survival through transcription factors S6K1, 4EBP1, and PPARg.…”
Section: Pbi-4050 Reduces Liver Fibrosismentioning
confidence: 99%